Sinergi Disiplin dan Lingkungan Kerja: Transformasi Kinerja Karyawan di PT Cipta Kridatama, Jakarta Selatan - Latif, Latif; Apriansyah, Muger; Agrasadya, Agrasadya; Sunarto, Ading; Syahneg, Syahneg (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
The purpose of this research is to determine the influence of discipline and work environment on employee performance at PT. Cipta Kridatama, South Jakarta, either partially or simultaneously. The method used is quantitative. The sampling technique used saturated sampling and the sample obtained in this study was 62 respondents. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing. The results of this research are that the influence (X1) has a significant effect on employee performance. By testing the hypothesis, the t count was obtained. There is a significant influence of work discipline on employee performance. From the results of the research conducted by the researcher, it was obtained that tcount was 1.128 < 1.672 ttable with a significance level of 0.264 > 0.05, meaning that Ho was rejected and H₁ was accepted. there is an influence of the work environment on the performance of PT employees. Create Kridatama. It is known that the significance value for the influence of the work discipline variable (X1), work environment (X2) simultaneously on the employee performance variable (Y) is 0.000 < 0.05 and the Fcount value is 16.244 > Ftable 3.156 so the author concludes that Ha is accepted and H0 is rejected. This means that the independent variables, namely work discipline and work environment, influence jointly or simultaneously on the performance of PT employees. Create Kridatama. Based on the output results in table 4.26, it is known that the Adjusted R Square value is 0.333. This result shows that 33.3% means that the influence of work discipline and work environment variables simultaneously influences employee performance variables. Meanwhile, the remaining 66.7% is influenced by other variables.